Toward a Structural Account of Conservativity - Romoli, Jacopo (Proceedings of Sinn und Bedeutung, 2019)
In this paper I propose a structural account of conservativity, which derives it as a byproduct of the syntax-semantics interface. In this approach, the reason for the absence of non-conservative determiners from natural languages is that in entering chain relations in the syntax, they would either lead to trivial meanings (in a sense to be made precise) or to quantificational clauses truth-conditionally equivalent to ones created by regular conservative determiners. In the latter case, I will argue that they do in fact exist but they are undetectable. As for the former case, I will argue that they are excluded because they lead to triviality, either formulated in terms of a constraint against ‘pointless’ lexical items, or with a notion of logical triviality which leads to ungrammaticality (Gajewski, 2002). Finally, I will explore two possible principles that should be coupled with either of the two: (1) DPs always move (2) DPs should always be moveable and will give some arguments for adopting the first principle in (1).